Inter-Industry Technology Flows and Productivity Growth - Scherer, F. M. (The Review of Economics and Statistics, 1982)
An unusually rich data set was tapped to explore the relationship between research and development (R and D) and productivity growth. The most-important finding is that, with disaggregated data, the wrong lag hypothesis is not supported: there is no clear indication that the productivity slump of the 1970s resulted from a decrease in the marginal productivity of R and D. Also important is the evidence of substantial returns to used R and D, i.e., from internal-process work and the purchase of R and D-embodying products, but not (at least in industries with productivity indices based upon physical output or comprehensive price deflators) to the performance of product R and D. Given the fact that three-fourths of all industrial R and D is product-oriented, studies that fail to distinguish between the origination and use of R and D may suffer from appreciable specification errors. Further research using improved R and D and (especially) productivity data is plainly needed, among other things, to clarify the mystery of why estimated R and D-productivity relationships differ for productivity-data subsets of varying quality. 15 references, 3 tables.